Teaching Methods Implemented by the Lecturers of English Education Department Universitas Muhammadiyah Yogyakarta to Develop Students’ Critical Thinking - Hendras Ayu Wulansari (PBI 15 UMY 033, 2015)
*33 There are many teaching methods used by lecturers to develop students’ critical thinking. The implementation of teaching methods in Interpretive Reading and Argumentative Writing class, the syllabus and the students’ activity in class tend to the characteristic of critical thinking skill. Critical thinking helps students make conclusion and clear a path for original thoughts. In addition, through critical thinking skills social workers can help people from all walks of life and come across people or populations with experiences, ideas and opinions that often vary from their own.Therefore, based on these phenomena the researcher was interested in conducting the research that focuses on discovering and describing teaching methods implemented by the lecturers of English Education Department UMY to develop students’ critical thinking. There is one research question presented in this study: what are the teaching methods implemented by lecturers of EED UMY to develop students’ critical thinking? This research used qualitative research design. To answer that research question, the researcher conducted an observationin class D batch 2014 in the subject matter of interpretive reading and argumentative writing. In addition, the researcher conducted an interview with two participants from the observed class. The data collected were transcribed, categorized and analysed. Then, the result of the observation and interview showed that there were three teaching methods implemented in the classroom namely: deep dialogue method, vi socratic method, and collaborative learning method. Furthermore, in teaching methods that developed students’ critical thinking there were two most used teaching methods to develop students’ critical thinking, these methods were socratic method and collaborative learning method. In Socratic Method, the activities which were employed by the lecturer in this method close book journal activity and drawing story activity. Those activities facilitated to get students’ hypothesis and to make students more think critically. In collaborative learning method, one of these activities in this method was the lecturer usually asked the students to make small group learning. From small group Learning, absolutely it was found that there were different perspectives and different points of view from each member in group which might cause group conflict and make critical thinker.